2013
DOI: 10.7251/els1317001r
|View full text |Cite
|
Sign up to set email alerts
|

Morlet Wavelet UDWT Denoising and EMD based Bearing Fault Diagnosis

Abstract: Abstract-Bearing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…It was reported that soft thresholding might result in the loss of useful information; therefore, hard thresholding was preferred for de-noising. The bearing fault signal, which was de-noised by the undecimated discrete wavelet transform (UDWT), was decomposed by empirical mode decomposition (EMD) into a set of intrinsic mode functions (IMFs) [10], [11]. The fast Fourier transform (FFT) of the specific IMF could clearly reflect the characteristic frequency of the fault.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that soft thresholding might result in the loss of useful information; therefore, hard thresholding was preferred for de-noising. The bearing fault signal, which was de-noised by the undecimated discrete wavelet transform (UDWT), was decomposed by empirical mode decomposition (EMD) into a set of intrinsic mode functions (IMFs) [10], [11]. The fast Fourier transform (FFT) of the specific IMF could clearly reflect the characteristic frequency of the fault.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Machine learning algorithms have often been used as classifiers to distinguish faulty conditions from the normal condition. The relative spectral entropy and gravity frequency of the envelope spectrum were used as the two-dimensional vector features for the K-nearest neighbor recognition [11]. The envelope analysis based on an energy operator was reportedly better than the envelope demodulation of Hilbert transform in terms of speed and accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, even EMD combination techniques are unreliable in noisy environments. Therefore, to effectively apply enhanced signal analysis techniques to non-stationary vibration signals, a proper pre-processing method to reduce noise is required, such as narrowband demodulation [36] or discrete wavelet transform (DWT) [37,38]. Applying those de-noising methods effectively reduces the measurement noise, but the original informative signal is also distorted by the attenuation of a narrow bandpass filter in narrowband demodulation or the threshold in DWT-based de-noising.…”
Section: Introductionmentioning
confidence: 99%
“…Sawalhi [27] combines MED with SK to enhance the rolling bearing failure. Raj [25] combines EMD with wavelet de-noising for fault diagnosis of bearings. Although much work has been done, there are still many shortcomings in bearing fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%